Coenzyme Q10 Regulation of Apoptosis and Oxidative Stress in H(2)O(2) Induced BMSC Death by Modulating the Nrf-2/NQO-1 Signaling Pathway and Its Application in a Model of Spinal Cord Injury - Li, Xing (Oxid Med Cell Longev, 2019)
Spinal cord injury (SCI) has always been considered to be a devastating problem that results in catastrophic dysfunction, high disability rate, low mortality rate, and huge cost for the patient. Stem cell-based therapy, especially using bone marrow mesenchymal stem cells (BMSCs), is a promising strategy for the treatment of SCI. However, SCI results in low rates of cell survival and a poor microenvironment, which limits the therapeutic efficiency of BMSC transplantation. Coenzyme Q10 (CoQ10) is known as a powerful antioxidant, which inhibits lipid peroxidation and scavenges free radicals, and its combined effect with BMSC transplantation has been shown to have a powerful impact on protecting the vitality of cells, as well as antioxidant and antiapoptotic compounds in SCI. Therefore, we aimed to evaluate whether CoQ10 could decrease oxidative stress against the apoptosis of BMSCs in vitro and explored its molecular mechanisms. Furthermore, we investigated the protective effect of CoQ10 combined with BMSCs transplanted into a SCI model to verify its ability. Our results demonstrate that CoQ10 treatment significantly decreases the expression of the proapoptotic proteins Bax and Caspase-3, as shown through TUNEL-positive staining and the products of oxidative stress (ROS), while increasing the expression of the antiapoptotic protein Bcl-2 and the products of antioxidation, such as glutathione (GSH), against apoptosis and oxidative stress, in a H(2)O(2)-induced model. We also identified consistent results from the CoQ10 treatment of BMSCs transplanted into SCI rats in vivo. Moreover, the Nrf-2 signaling pathway was also investigated in order to detail its molecular mechanism, and the results show that it plays an important role, both in vitro and in vivo. Thus, CoQ10 exerts an antiapoptotic and antioxidant effect, as well as improves the microenvironment in vitro and in vivo. It may also protect BMSCs from oxidative stress and enhance their therapeutic efficiency when transplanted for SCI treatment.